Peningkatan Konsep Kreatif Fotografi Produk Desa Lengkong Kulon Sebagai Pengembangan UMKM - Rezki Gautama Tanrere; Alexandra Sekar Dita Listyorini; Francois William Jordy; Monica Monica (Universitas Pelita Harapan, 2022)
Lengkong Kulon, located in Pagedangan District, Tangerang, keeps and preserves their traditions in the midst of modernization that is growing today. Lengkong Kulon itself has the potential to support their economic activities in various Micro, Small and Medium Enterprises (MSME) engaged in the culinary field by having its own characteristics, namely Arabic culinary specialties such as Kebuli and Ka'ak Cakes as its attractions. However, in the midst of urban progress, developments of MSMEs are very minimal in terms of promotion. This problem can be caused by limited capital, human resources, to poor marketing management, but there are also other problems such as the lack of packaging aesthetics and photos of MSME products which have an impact on promotional activities not going well, so that MSME products are less well known by the public. large. From this problem, the solution provided by our research team is to improve the creative concept of product photography in Lengkong Kulon as a means of developing MSMEs. In order to improve the quality of product photos in Arabic culinary specialties as a characteristic of the village, it is necessary to design a visual product photo that is attractive and creative in each presentation to promotion, and is carried out systematically through three stages, starting from the inspiration stage, ideation stage, and implementation stages. The research team hopes that, through the quality and concept of photos in visual design to better and more attractive promotions, they can introduce and increase the interest of consumers and the wider community that Lengkong Kulon has its characteristics and a variety of interesting MSME product potentials, on the other hand it can also help improving the economy and welfare of the people of Lengkong Kulon.abstract in bahasaDesa Lengkong Kulon yang terletak di Kecamatan Pagedangan, Tangerang menyimpan dan melestarikan tradisi mereka di tengah modernisasi yang semakin berkembang dewasa ini. Desa Lengkong Kulon sendiri memiliki potensi dalam menunjang aktivitas ekonomi mereka pada berbagai UMKM yang bergerak pada bidang kuliner dengan memiliki ciri khas tersendiri yaitu kuliner khas Arab seperti Kebuli dan Kue Ka’ak sebagai daya tariknya. Namun di tengah kemajuan kota, perkembangan UMKM desa sangat minim dari segi promosinya. Masalah ini dapat disebabkan oleh keterbatasan modal, sumber daya manusia, hingga pengelolaan marketing yang buruk, namun terdapat pula masalah lainnya seperti kurangnya estetika kemasan dan foto produk UMKM yang berdampak pada kegiatan promosi tidak berjalan dengan baik, sehingga produk-produk UMKM kurang dikenal oleh masyarakat luas. Dari masalah tersebut, solusi yang diberikan oleh tim peneliti adalah melakukan peningkatan konsep kreatif fotografi produk Desa Lengkong Kulon sebagai sarana pengembangan UMKM. Agar peningkatan kualitas foto produk pada kuliner khas Arab sebagai ciri khas desa tersebut dapat berlangsung dengan baik, maka dilakukan perancangan visual sebuah foto produk yang menarik dan kreatif dalam setiap penyajiannya hingga promosi, serta dilakukan secara sistematis melalui tiga tahapan, dimulai dari tahap insipiration,tahap ideation, dan tahap implementation. Harapan besar tim peneliti, melalui kualitas dan konsep foto dalam perancangan visual hingga promosi yang baik dan lebih menarik, dapat memperkenalkan dan menambah ketertarikan konsumen maupun masyarakat luas bahwa Desa Lengkong Kulon memiliki ciri khas serta beragam potensi produk UMKM yang menarik, disisi lain dapat pula membantu peningkatan perekonomian dan kesejahteraan masyarakat Desa Lengkong Kulon.